Application of Lean Thinking to Minimize Waste at The Warehouse of PT. Aerojasa Cargo - Mochammad Arif Hernawan; Tenaka Budiman; Nabila Harum Sholifa; Shinta Paulia (Jurnal Ilmu Multidisiplin, 2025)
This research aims to identify types of waste and minimize the causes of waste in warehouse operational activities, spanning from the receiving process to the shipment of goods at PT. Aerojasa Cargo Jurumudi warehouse. The problems in the company arise due to non-value-added warehouse operational activities (waste). The major types of waste identified are motion waste, overprocessing, and waiting. The method used is a qualitative method with a lean thinking approach, supported by Value Stream Mapping (VSM) tools and complemented by fishbone diagrams to identify the root causes of waste problems. Research data were obtained through direct observation and interviews. The results show that waste occurs because of a lack of structured task distribution among operators and insufficient availability of material handling equipment. Recommendations for improvement include assigning clear and structured tasks and responsibilities to each employee, evaluating the use of necessary materials, and adding equipment as needed.